A pilot investigation of the potential for incorporating lifelog technology into executive function rehabilitation for enhanced transfer of self-regulation skills to everyday life. Issue 4 (19th May 2018) - Cuberos-Urbano, Gustavo; Caracuel, Alfonso; Valls-Serrano, Carlos; García-Mochón, Leticia; Gracey, Fergus; Verdejo-García, Antonio
ABSTRACT: The objective of the study was to identify the potential target and effect size of goal management training (GMT) enhanced with life-logging technology compared with standard GMT on a range of possible primary outcomes reflecting cognitive and ecological aspects of executive functioning and quality of life. Sixteen patients with acquired brain injury involving executive dysfunction were randomly allocated to one of the two interventions: seven weeks of GMT ( n  = 8), or seven weeks of GMT+Lifelog ( n  = 8). Outcome measures included a battery of executive function tests, the Dysexecutive Questionnaire (DEX) and the Quality of Life after Brain Injury scale (QOLIBRI), measured pre- and post-interventions. Within-group changes were assessed with related-samples t -tests and estimation of effect sizes. GMT+Lifelog was associated with significant changes, of medium to large effect size, in response inhibition (Stroop), multitasking (Strategy Application and Multiple Errand tests), DEX Intentionality and Positive Affect subscales and QOLIBRI Daily Life and Autonomy, subscales. GMT alone was associated with significant changes of overall quality of life. It was concluded that GMT+Lifelog holds promise to optimise the impact of GMT on executive dysfunction and quality of life.